Calculați: (x+1)(x-1)(x^2+1)(x^4+1)(x^8+1)...(x^2^100+1) .
tudor2001:
Da asa
Răspunsuri la întrebare
Răspuns de
3
[tex]\rm (x+1)(x-1)(x^2+1)(x^4+1)(x^8+1)....({x^{2}}^{100}+1)= \\ \\
(x^2-1)(x^2+1)(x^4+1)(x^8+1)....(x^{200}+1)= \\ \\
(x^4-1)(x^4+1)(x^8+1)....(x^{200}+1)= \\ \\
(x^8-1)(x^8+1)....(x^{200}+1)= \\ \\
..... \\ \\
(x^{200}-1)(x^{200}+1)= \\ \\
\boxed{\rm Raspuns:x^{400}-1}[/tex]
Alte întrebări interesante
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Fizică,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Chimie,
10 ani în urmă
Matematică,
10 ani în urmă